1993
DOI: 10.1111/j.1440-1681.1993.tb01729.x
|View full text |Cite
|
Sign up to set email alerts
|

Five Year Prospective Study on Blood Pressure and Maximal Oxygen Uptake

Abstract: 1. The relationship between physical fitness (maximal oxygen uptake VO2max) and incidence of hypertension was investigated through a prospective study for a total of 16,525 human-years of observation. 2. This study involved 3305 Japanese males whose blood pressure (BP) was normal when they received their first physical examination before the age of 50. They were monitored from 1983 to 1988. The BP of 425 subjects was diagnosed as hypertension in the fifth year. 3. Fitness levels were divided into quintiles acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…In a 1-to 12-year retrospective study of men and women aged 20 to 65 years with no history of hypertension, Blair et al 18 showed that subjects with low levels of V · O 2peak were at higher risk for developing hypertension than were those with high V · O 2peak . Sawada et al 19 further showed in a 5-year longitudinal study of men aged 50 years and older that subjects with increased V · O 2peak were less likely to have increased blood pressure after 5 years than those with unchanged or decreased V · O 2peak . In the current study, the high reduction in SBP occurred in the subjects with increased V · O 2peak .…”
Section: Discussionmentioning
confidence: 99%
“…In a 1-to 12-year retrospective study of men and women aged 20 to 65 years with no history of hypertension, Blair et al 18 showed that subjects with low levels of V · O 2peak were at higher risk for developing hypertension than were those with high V · O 2peak . Sawada et al 19 further showed in a 5-year longitudinal study of men aged 50 years and older that subjects with increased V · O 2peak were less likely to have increased blood pressure after 5 years than those with unchanged or decreased V · O 2peak . In the current study, the high reduction in SBP occurred in the subjects with increased V · O 2peak .…”
Section: Discussionmentioning
confidence: 99%
“…In the former, the relative risk was 1.5 times higher than in the latter. 14) . This is a cohort study involving a 5-year follow-up of 3,305 Japanese males in whom exercise tests were conducted.…”
Section: Fitness and Hypertensionmentioning
confidence: 99%
“…On the other hand, the aerobic physical fitness level is also independently associated with the risk factors for the disease (10,12). Since there are some evidences that the level of physical activity and aerobic physical fimess is one of the causes of abdominal obesity (3,8), it is worthwhile to evaluate whether or not both factors are independently related to the risk factors for CHD.…”
Section: Introductionmentioning
confidence: 99%